(untitled) (Champaign, 2009)
This book includes many parts: the aim of a good translation, how editors choose translators, translation contracts, estabilshing boundarIes, translation problemsand solutions, the editing process,...
Keywords: Biên dịch và phiên dịch,Translating and interpreting